(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Acupuncture is a traditional Chinese treatment for pain. Acupuncture is a 3000-year-oldtraditional therapy from China. Electroacupuncture is similar to traditional acupuncture in that it uses electrical stimulation. It works similarly to orthodox acupuncture in that it excites the same regions. As with conventional acupuncture, needles are inserted at designated points on the body. The needles are then coupled to a gadget that leverages tiny clips to establish a consistent electric pulse. These devices alter the frequency and strength of the impulses based on the condition being treated. Electroacupuncture uses two or more needles at the same time to allow impulses to pass from one needle to the next. This can be performed by using a standard TENS machine attached to the needles via cables and crocodile clips by using commercially available electroacupuncture machines.